The Song of Bernadette - Perlberg, William, 1899-1969.; Jones, Jennifer, 1919-2009.; Eythe, William, 1918-1957.; King, Henry, 1886-1982.; Werfel, Franz, 1890-1945.; Twentieth Century-Fox Film Corporation (Beverly Hill, CA : Twentieth Century Fox Home Entertainment, 2003)
Until a miracle changes their minds, church and state officials persecute a simple, ingenuous peasant girl who claims to have seen a vision of the Virgin Mary.
Based on the novel by Franz Werfel.
DVD release of the 1943 motion picture; copyright renewed 1971.
Directed by Henry King ; produced by William Perlberg ; screenplay by George Seaton.
Jennifer Jones, William Eythe, Charles Bickford, Vincent Price, Lee J. Cobb, Gladys Cooper.
DVD format.
Closed-captioned
Keywords: Bernadette, -- Saint, -- 1844-1879 -- Drama; Shrines -- France -- Lourdes -- Drama; Religious films; Feature films -- France; Video recordings for hard of hearing people